Serotonin and Dopamine Blood Levels in ADHD-Like Dogs - Ángela González-Martínez; Susana Muñiz de Miguel; Noemi Graña; Xiana Costas; Francisco Javier Diéguez (Animals, 2023)
As with humans, dogs can suffer from attention deficit hyperactivity disorder-like (ADHD-like) behaviors naturally and exhibit high levels of hyperactivity/impulsivity and attention deficit problems, making the domestic dog a potential animal model for ADHD. ADHD has a very complex pathophysiology in which many neurotransmitters are involved, such as serotonin and dopamine. The aim of the study was to evaluate serum serotonin and dopamine levels in dogs with ADHD-like symptomatology. Fifty-eight dogs were studied, of which, thirty-six were classified as ADHD-like after physical and behavioral assessments. Additionally, the dogs’ owners performed a series of scientifically validated questionnaires which included C-BARQ, the Dog Impulsivity Assessment Scale, and the Dog-ADHD rating scale. Serum from every animal was collected after the behavioral assessments and analyzed with commercial ELISA tests for serotonin and dopamine determination. Kruskal–Wallis tests and Lasso regressions were applied to assess the relationships between both neurotransmitters and the ADHD-like behaviors (as assessed by clinical evaluation and through the different questionnaires). The dogs clinically classified as ADHD-like showed lower serotonin and dopamine concentrations. Further, serotonin and dopamine levels were also linked to aggression, hyperactivity, and impulsivity. Decreased serotonin concentrations were also related to fear, attachment, and touch sensitivity. Finally, it must be noted that our data suggested a strong relationship between serotonin and dopamine and ADHD-like behaviors.